2014
DOI: 10.1007/s12264-014-1469-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain dopaminergic system changes in drug addiction: a review of positron emission tomography findings

Abstract: Dopamine (DA) is considered crucial for the rewarding effects of drugs of abuse, but its role in addiction remains unclear. Positron emission tomography (PET) is the fi rst technology used for in vivo measurement of components of the dopaminergic system in the human brain. In this article, we review the major fi ndings from PET imaging studies on the involvement of DA in drug addiction, including presynaptic DA synthesis, vesicular monoamine transporter 2, the DA transporter, and postsynaptic DA receptors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…Chronic use of cocaine appears to lead to dysregulation of brain dopaminergic system (Hou et al 2014). Several studies have shown that DA at high concentrations may participate in neurodegenerative processes, such as in Parkinson's disease (Ahlskog 2007;Ravina et al 2012).…”
Section: Dopamine Toxicity Caused By Cocaine Addictionmentioning
confidence: 99%
“…Chronic use of cocaine appears to lead to dysregulation of brain dopaminergic system (Hou et al 2014). Several studies have shown that DA at high concentrations may participate in neurodegenerative processes, such as in Parkinson's disease (Ahlskog 2007;Ravina et al 2012).…”
Section: Dopamine Toxicity Caused By Cocaine Addictionmentioning
confidence: 99%
“…These conclusions are well supported by ours. In addition, the dopaminergic system in the NAc controls drug addiction, which has similarities to the OSCI model [10]. Moreover, the NAc receives inputs from several regions of the limbic system (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Nicotine, like other drugs of abuse, is associated with abnormal function in the mesolimbic dopamine system and reward-related brain areas, such as the ventral tegmental area, prefrontal cortex, nucleus accumbens, amygdala, and hippocampus [17]. The dorsolateral prefrontal cortex (dlPFC) is widely acknowledged to be an effective stimulation target, as it has been associated with cue-provoked smoking craving [18], which is the primary trigger of relapse [19].…”
Section: Rationale For Using Nibs To Treat Nicotine Addictionmentioning
confidence: 99%